1995
DOI: 10.1128/iai.63.8.3213-3217.1995
|View full text |Cite
|
Sign up to set email alerts
|

Protection of C3H/He mice from experimental Borrelia burgdorferi infection by immunization with a 110-kilodalton fusion protein

Abstract: A 110-kDa Borrelia burgdorferi fusion protein, Escherichia coli expressing the fusion protein, transformed E. coli lacking the fusion protein insert, and lyophilized whole B. burgdorferi bacteria were compared for immunogenicity in C3H/He mice. Immunized mice were challenged with a variety of isolates from the United States or the European isolate P/Gau 3 weeks following the last inoculation. An average of 76.7% of the mice immunized with 25 g of lyophilized whole B. burgdorferi cells were protected from infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…These antigens are OspA (5,7,26,29), OspB (8,22), OspC (21,22), and OspF (18). Additionally, a nonsurface fusion protein with a molecular mass of 110 kDa containing a truncated HSP70 (2) has been reported to be protective, and studies have suggested that P39, also known as BmpA, may also be protective (15,25). OspA has been the subject of the most complete studies as an effective protective immunogen in experimental animals (and under evaluation in humans), although some recent data imply that it may have some limitations as a vaccine candidate.…”
mentioning
confidence: 99%
“…These antigens are OspA (5,7,26,29), OspB (8,22), OspC (21,22), and OspF (18). Additionally, a nonsurface fusion protein with a molecular mass of 110 kDa containing a truncated HSP70 (2) has been reported to be protective, and studies have suggested that P39, also known as BmpA, may also be protective (15,25). OspA has been the subject of the most complete studies as an effective protective immunogen in experimental animals (and under evaluation in humans), although some recent data imply that it may have some limitations as a vaccine candidate.…”
mentioning
confidence: 99%
“…Although less extensively studied than GroEL, DnaK homologues of many bacterial pathogens have been found to be immunogenic in humans or animals (1,2,5,8,10,47). Furthermore, as has been shown by the experimental infection of mice with Borrelia burgdorferi, immunization with proteins containing DnaK-specific sequences may protect against microbial infection (4).…”
mentioning
confidence: 99%